Management of acute diarrhea in children hospitalized at the Hospital EsSalud Grau III - Miranda Candelario, Javier (2011)
Objetive: Evaluate the management of children hospitalized with acute diarrhea. Method: A retrospective observed and analyzed trial in hospitalized diarrhea during 2005, at Pediatric Service Grau Hospital. Results: 194 patients were enrolled, 57% males and 43% females. The most important group was major lactants 43% and pre-schoolchildren 42%. We had 84% well nutried. 61% received exclusively breast-feeding and 22% got antibiotic itself. They were hospitalized: 88%, with moderate, 10% mild and 2% severe dehydration. From 16 dysenteric diarrhea, 15 Received ATB. From 178 watery diarrhea, 80 were bacterial all of them got antibiotics, and 98 were viral: 73 without ATB and 25 with ATB for abrupt evolution. To decide ATB: value of fecal leukocytes, CBC and appearance clinical. It started with + 40 fecal leukocytes and some one with less than 20. All 194 patients received hydration EV, 19% started refeeding before 4º hours, 88% accepted ranitidina, 76% dimenhidrinato and 62% ATB, specially amikacina 61% and cloranfenicol 19%. Conclusions:• There aren’t diagnostic tests fastest for rotavirus, and others like fecal lactoferrin.• We noted sub utilization of oral dehydration therapy. • We found excess intravenous therapy and other medicaments.• Early Refereeing is not right.• Excessive use of antibiotics. “This study reflexes the kind of work of most of Hospitals of our country”.